Design and control of a motor wheel system controlled by smartphone. Issue 1 (July 2020) - Asus, Z; Mat Razi, M F I; Mahmudin, M F; Che Daud, Z H; Mazali, I I; Ardani, M I
Abstract: The purpose of this project is to design a wheel system controlled by smartphone for multiple utilisations and determine its efficient control. The motor wheel system is equipped with four mecanum wheels with ten movements: forward, reverse, left, right, clockwise, counter-clockwise, and four on diagonal. PID control which is a closed-loop control was implemented to regulate the speed of the wheel system. The system is equipped with Bluetooth and a mobile application was developed as its user interface. Two control mode was developed in this project which is the precision mode where the user controls the wheel system manually using the smartphone as a control panel and another mode is the following mode where smartphone internal gyroscope and accelerometer are combined together to move the wheel system automatically with respect to the user body movements. CAD model of the design is developed in Solidworks and finite element analysis is done using CAE. FEA analysis is studied and discussed with focus on the critical location of the design. The full-size prototype of the design is developed and tested in normal running conditions. The system is proven to be reliable to carry loads and can be controlled efficiently by smartphone.